(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The aim of the study is to develop and evaluate sustained release formulations containing dinalbuphine sebacate (DNS) for the treatment of rheumatoid arthritis (RA). Materials and Methods: A DNS-loaded microemulsion was optimized using pseudoternary phase diagrams and Minitab software. This was incorporated into a 2% w/v chitosan gel for enhanced skin delivery. The formulation was characterized for particle size transmission electron microscopy, rheology, and stability. In vitro skin permeation was tested using Franz diffusion cells with human cadaver skin, and in vivo anti-arthritic efficacy was evaluated in complete Freund’s adjuvant-induced arthritic rats. Results and Discussion: The DNS-loaded chitosan gel showed favorable rheology, sustained release, and enhanced skin retention. Treated arthritic rats had a significant reduction in paw swelling, with one gel reducing inflammation by 57.5%. Inflammatory and liver biomarkers improved, and histology confirmed preserved joint structure with minimal inflammation. The formulation remained stable over 6 months. Conclusion: DNS-loaded chitosan gel offers a promising localized treatment for RA, providing prolonged pain relief while reducing systemic exposure and opioid side effects. It presents a non-invasive alternative for managing chronic inflammatory pain.